PERCEIVED RISKS IN ENTREPRENEURIAL PROCESS AMONG CULINARY SMEs - WINONA JANICE (19215058), VERENCIA
Perception towards risk may influence entrepreneurs to start their business and also the willingness to take risks throughout the business process. Timmons Model of Entrepreneurial Process considers team, opportunity, and resources as three components for a successful new business. By using it as theoretical basis, this research would like to assess the perceived risks of culinary entrepreneurs in their entrepreneurial process. Culinary SMEs play a huge role in boosting the economic growth of Indonesia, especially for a creative industry like Bandung. The research is expected to provide insight for the business starters, help them facing the challenges in starting and running the business, so that they can predict and prepare themselves if they later face these similar perceived risks. The focus is to describe how entrepreneurs perceive risks in their own culinary business and to identify their responses or the capacity they need to overcome those risks. This study considers perceived risk that is not only limited to financial loss or opportunity, but also related to social capital and resources. In order to address this issue, this study uses qualitative approach and conducts semi-structured interviews with 11 small and medium entrepreneurs operating in culinary industry in Bandung. The purpose of the interview would be to know how entrepreneurs perceive the risks in team, opportunity, and resources aspects of their business. The results of this study shows that there are some perceived risks of culinary SMEs in opportunity factor of their entrepreneurial process, which are: business location selection, the effects of following food trends, and partnering with GO-FOOD and GrabFood. The perceived risk about team is the team member selection. For the resources, the perceived risks are around: recipe disclosure, food cost, resource efficiency, stock control, fraud risk, employee risk, and supply risk. Therefore, the capacities and responses needed to face the perceived risks in opportunity are: choosing the right product and target market, also to always do research first. In handling the perceived risk in team, entrepreneurs have to develop a skilled and competent team. The capacities for managing the perceived risks in resources are: have a clear system, maintain a competitive profit margin, resource optimization, employee management, and agreement with suppliers. In majority, food cost and partnering with GO-FOOD and GrabFood are the perceived risks that are most likely concerned by the entrepreneurs. The rising cost of food as well as the miscalculations of profit sharing with GrabFood are the example. The impact that become the entrepreneursÃ‚Â’ biggest worry is the decline in sales. The capacity to choose the right product and target market is considered important as well as maintaining a competitive profit margin to make sure the business survive. Overall, the perceived risks of culinary SMEs exist and affecting their entrepreneurial process. The entrepreneurs shared their responses and capacities of handling the perceived risks. The suggestion for future research regarding this topic is the quantitative study and relationship or correlation between the perceived risks in opportunity, team, and resources aspects of entrepreneurial process.